Effect of Lower Extremity Exercise on The Borg Scale in Chronic Obstructive Pulmonary Disease - Ghamal Arif Hanafiah; Amira P Tarigan; Pandiaman Pandia; Putri C Eyanoer (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
COPD patients tend to experience complaints shortness of breath, limb muscle fatigue and distress in an effort in activities that result in a decrease in quality of life and inhibit daily activities. This situation will eventually cause the patients to experience fatigue faster and fall into a deconditioning state. The Borg scale is a way to measure the intensity level of physical activity using a ratio scale size. This study aimed to assess the effect of lower limb endurance training on the Borg Scale of COPD patients. A quasi-experimental study conducted on 20 patients with COPD group C and D which underwent lower extremity resistance training. The Borg scale was assessed before and after training, with statistical analysis performed by the Mann Whitney-Test. There was an effect on lower extremity resistance training on the Borg Scale of COPD patients in the form of a significant decrease in the Borg Scale value where in the effort parameters. Before training, the Borg Scale score of COPD patients was 9 and 15, decreased to 1 and 13 after training. While tired feet, before training was 5 which decreases to 3 after training and shortness of breath, before training is 7 which decreases to 4 after training. There is a significant improvement in the value of the Borg Scale of COPD patients after undergoing a lower limb endurance training program. There were no significant Borg scale differences between Group C and Group D after undergoing a lower limb endurance training program.